Russian Physicians in an Era of Reform and Revolution, 1856-1905 - Nancy Mandelker Frieden (Princeton University Press, 2014)
Physicians in pre-Revolutionary Russia shared many of the characteristics of the educated elite. As social reformers they served the common folk in both remote villages and urban slums, as technical experts they devised and implemented pioneering community health programs, and as political activists they helped to precipitate the Revolution of 1905. Various interpretations of the Russian intelligentsia help to explain their actions: some sympathized with peasants and workers because they themselves were of humble origin, or because their work exposed dire social need, or because they felt a debt to those whose toil supported their education; medical scientists were especially receptive to the positivism and scientific materialism current in that era; and "free professionals" were attracted to the movement for constitutional reform. The study of Russian physicians is thus an excursion into the world of educated Russians in a period of rapid social change.